상업적 살균 기술 적용에 따른 착즙 유자액의 품질 특성 - 이창헌(Changheon Lee); 문승민(Seungmin Moon); 차은송(Eunsong Cha); 심진하(Jin Ha Sim); 김진현(Jin Hyeon Kim); 정두연(Duyun Jeong); 유대웅(Daeung Yu) (Han'guk Sikp'um Yŏngyang Kwahakhoe chi, 2023)
본 연구는 상업적 살균 기술 적용에 따른 착즙 유자액의 미생물, 항산화력 및 이화학적 특성 분석을 통한 최적 상업적 살균 기술을 탐색하고자 하였다. 상업적 살균 기술인 LTLT, HTST 및 HPP 처리 후 4°C에서 84일간 저장하며 분석한 결과, 미생물은 착즙 유자액의 낮은 pH와 높은 항산화 물질 함량으로 인해 저장 기간에 살균 미처리군(대조군) 및 살균 처리군 모두 미검출되었다. 이화학적 특성으로 pH는 유의미한 차이가 없었으며, 가열 처리로 인해 당도(°Brix) 및 색차에서 HTST 처리군에서 유의미한 차이를 나타내었다(P< 0.05). 항산화력은 DPPH 라디칼 소거능에서 저장 84일 차에 HPP 처리군에서 4.52±0.30, HTST 처리군에서 0.49± 0.00으로 약 90% 차이를 보였다. 이러한 결과를 바탕으로 착즙 유자액의 저장 기간 연장과 항산화력 및 이화학적 특성을 최대한 유지하는 상업적 살균 기술은 비가열 처리 살균 기술인 HPP가 가장 효율적이다. The objective of this study was to find the optimal commercial sterilization technology for squeezed yuzu (Citrus junos) juice by analyzing microbes, antioxidant activity, and physicochemical properties after commercial sterilization [LTLT (low temperature long time) at 60°C for 30 min, HTST (high temperature short time) at 75°C for 1 min, and HPP (high pressure processing) at 500 MPa for 3 min]. Juices were stored for 84 days at 4°C after sterilization, during which no microbes were detected. Juice pH was not a significant difference regardless of treatments, but significant differences were observed in °Brix and color values between HTST and LTLT treatments and HPP treatment due to the conversion of pectin into reducing sugars and carotenoid pigment changes during thermal treatments. HPP treatment resulted in 90% and 10% higher DPPH radical scavenging activity and total phenol contents, respectively, compared to HTST treatment, which was attributed to the destruction of phenol and vitamin C during thermal treatment. This study shows that HPP was the most effective sterilization technology because it effectively maintained antioxidant activity and physicochemical properties and extended the shelf life of squeezed yuzu juice. Furthermore, our results suggest HPP should be considered the sterilization technology of choice in the juice industry. KCI Citation Count: 0